Lead induced toxicity in Labeo rohita: cortisol, antioxidant enzymes and liver biomarker levels - Quratulain, .; Ismat, N.; Kousar, T.; Ullah, M.; Lubna, .; Ali, K.; Khan, T. M.; Ali, S.; Farooq, U.; Azmat, H. (Regulatory Mechanisms in Biosystems, 2025)
The long-term persistence of heavy metals in water bodies makes their contamination a serious concern. Among heavy metals, lead (Pb 2+ ) is most abundant in the aquatic environment, where its negative effects on the fauna are severe. This work aims to investigate the median-lethal concentration (LC 50 ) of lead against Labeo rohita , and lead-induced oxidative stress by analyzing antioxidant enzymes (SOD, CAT), cortisol profile, lipid peroxidation and aminotransferases activity (ALT, AST and ALP). The final value of LC 50 determined by probit analysis was 71.58 ± 0.61 mg/L. The results indicated that fish mortality is a function of Pb 2+ concentration and duration of exposure. After determination of LC 50 , experimental fish were treated with 1/3rd, 1/5th and 1/10th of LC 50 , with one control group for 28 days. The cortisol level was significantly increased from week 1 to 4. The maximum cortisol level observed was 124.95 ± 0.88 µg/m L . SOD and CAT activity significantly increased with increas e in the concentration and duration. The Pb-exposed groups showed a significant rise in lipid peroxidation (LPO) and liver enzyme activity. This study identified lead as a stress-inducing factor in fish. So, the use of lead should be reduced to protect valuable biodiversity. The study also reinforces the urgent need to monitor and regulate lead discharge into aquatic environments to safeguard aquatic biodiversity and protect public health through the food chain.